No such thing as the real world: Confronting ideology through critical translingual professional development. (April 2023) - Seltzer, Kate
Abstract : This article describes a year-long professional development (PD) series that invited three U.S.-based teachers of English, all of whom identified as white and monolingual English-speaking, to learn about translanguaging and other critical perspectives on language and the teaching of racialized bi/multilingual students. This paper features moments from the PD series wherein participants grappled with different elements of their teaching, from the policies they enforced to the assessment practices they upheld. Analysis of these moments shows how the PD series led teachers to (a) interrogate the so-called "real world" that teachers of English are ideologically called to prepare students for, and (b) envision an English classroom that eschews monoglossic approaches and invites students' translanguaging by emphasizing transparency and choice. This PD series holds potential for developing both exploratory language and literacy pedagogies and the stances of white, monolingual educators of racialized bi/multilingual students.